Morphological analysis of frontier villages in Cyprus - Edgu, Erincik; Comert, Zafer; Ozgece, Nezire (Univ Politecnica Valencia, 2018)
Borders may be built for security reasons however; they also demarcate administrative, economic, socio-cultural, ethnic or religious divergence. Borders change the destinies of the societies at both sides because they affect the process of urban development and delimit the economic and socio-cultural interactions. Cyprus has been experiencing an interrupted continuity along the border, i.e. green line, under the rule of UN that divides north from the south. In this regard, the aim of the study is to figure out how the de facto borders affect the configuration of villages upon their existing position. As a part of an ongoing research which investigates all eleven frontier villages and towns located along the border line, this paper only focuses on the morphological and syntactic comparison of four frontier villages. Within this context, initial exploration is about the village morphologies by means of Morphological Regions based on the evolutionary insights of Conzen (2004) and Whitehand (2009). Additionally, considering shifted centrality and transformed social gathering spaces, research discusses the applicability of the comparative analyses of syntactic and morphological methods in order to reveal the characteristics of the frontier villages. The preliminary findings of the research indicate that edge villages located along the green line have a controlled spatial development with dead ends and loop layouts, where the spatial configuration presents an introverted structure. On the other hand, villages divided by the green line, presents a relatively integrated spatial structure developed on both sides of the border, maintaining traditional centrality along with emphasizing forced territoriality.
24th International Seminar on Urban Form -- SEP 27-29, 2017 -- Valencia, SPAIN
Keywords: Urban morphology; fringe belts; edges; axiality; centrality